Pola Komunikasi Dalam Program Pengendalian Penyakit Tuberkulosis Pada Konsorsium Penabulu STPI IU Kabupaten Bekasi - Asmara, Tina; Syarah, Maya May; Susilowati, Susilowati (Prisani Cendekia Institute, 2024)
Tuberculosis (TB) is one of the top ten causes of death worldwide and is the leading cause of death from infectious agents. The high incidence of Tuberculosis in Indonesia is largely due to the lack of public understanding or knowledge about the disease. Although various educational efforts have been made, the level of public knowledge is still low and special and effective communication patterns are needed so that information about Tuberculosis can be well received by the community. The purpose of this study was to determine the communication patterns used in the Tuberculosis (TB) disease control program at the Penabulu Consortium of STPI IU Bekasi Regency. The method used in this research is descriptive qualitative method, this method provides an in-depth and detailed description of the research question through data collection and analysis. The results of this study indicate that the communication pattern used in the TB disease control program at the Penabulu STPI Consortium is group communication. Group communication patterns provide extensive education to the public about TB disease using the form of direct socialization, communicators in group communication patterns are cadres as a distributor of information about Tuberculosis Prevention Therapy (TPT), conveying information with visual media such as projectors and flip sheets to the public and patients.